2015
DOI: 10.3109/13880209.2015.1029054
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid-enriched extract fromEucommia ulmoidesleaves inhibits hepatic lipid accumulation through regulation of cholesterol metabolism in HepG2 cells

Abstract: CAEF is a promising dietary supplement to prevent obesity and dyslipidemia and the effects appear to be due, at least in part, to regulating cholesterol metabolism through inhibition of HMGCR in HepG2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…As to the lipid metabolism influence, chlorogenic acid is even characterized as “an anti-obesity natural molecule” [ 48 ], it is known to reduce hepatic triglycerides level in obese mice (at respectively high dose of 30–60 mg/kg) [ 5 ], and GW tincture exerts such effect in rats receiving ethanol (but at higher dose of 5 ml/kg) [ 49 ]. It has been shown recently that chlorogenic acid is one of the active ingredients in the crude herbal drug counteracting chronic ethanol-induced hepatic lipid accumulation through MAPK/SREBP-1c-dependent and -independent signalling pathways [ 50 ] and in vitro it increases the efflux of total cholesterol and triacylglycerols to the hepatocytes, inhibits HMG-CoA reductase activity [ 51 ]. In addition to chlorogenic acid, other hydroxycinnamic acids may mediate pharmacological activity of GW drugs.…”
Section: Resultsmentioning
confidence: 99%
“…As to the lipid metabolism influence, chlorogenic acid is even characterized as “an anti-obesity natural molecule” [ 48 ], it is known to reduce hepatic triglycerides level in obese mice (at respectively high dose of 30–60 mg/kg) [ 5 ], and GW tincture exerts such effect in rats receiving ethanol (but at higher dose of 5 ml/kg) [ 49 ]. It has been shown recently that chlorogenic acid is one of the active ingredients in the crude herbal drug counteracting chronic ethanol-induced hepatic lipid accumulation through MAPK/SREBP-1c-dependent and -independent signalling pathways [ 50 ] and in vitro it increases the efflux of total cholesterol and triacylglycerols to the hepatocytes, inhibits HMG-CoA reductase activity [ 51 ]. In addition to chlorogenic acid, other hydroxycinnamic acids may mediate pharmacological activity of GW drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Lonicera caerulea berry extract has been proven to reduce the cholesterol accumulation by regulating the related gene expression in the liver and the enzymatic activity of hepatic CYP7A1 in rats (Liu et al ., ). Particularly phenolic compounds such as polyphenols, chlorogenic acid, anthocyanins and catechins are generally believed to lower serum cholesterol level, decrease cholesterol and lipid accumulation and maintain the cholesterol balance in human by regulating the expression of cholesterol metabolism‐related miRNAs and activity of lipid metabolism‐related enzymes (Ogino et al ., ; Lee et al ., ; Milenkovic et al ., ; Hao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, in a very recent paper, Hao et al. 43 showed that the efflux of total cholesterol in HepG2 cells is increased by chlorogenic acid. Accordingly, in our study, an enhanced cholesterol efflux mediated by chlorogenic acid could have prevented the increase in the cholesterol cellular concentration due to the overexpression of HMGR and LDLR induced by quercetin.…”
Section: Resultsmentioning
confidence: 99%